2017
DOI: 10.3847/1538-4357/835/1/42
|View full text |Cite
|
Sign up to set email alerts
|

HESS J1427−608: AN UNUSUAL HARD, UNBROKEN Γ-Ray SPECTRUM IN a VERY WIDE ENERGY RANGE

Abstract: We report the detection of a GeV γ-ray source which is spatially overlapping and thus very likely associated with the unidentified very-high-energy (VHE) γ-ray source HESS J1427-608 with the Pass 8 data recorded by the Fermi Large Area Telescope. The photon spectrum of this source is best described by a power-law with an index of 1.85 ± 0.17 in the energy range of 3 − 500 GeV, and the measured flux connects smoothly with that of HESS J1427-608 at a few hundred GeV. This source shows no significant extension an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
(63 reference statements)
1
9
0
Order By: Relevance
“…No associated X-ray point source with similar column density was reported using XMM-Newton data (Fujinaga et al 2013). Above 3 GeV, a Fermi-LAT point source was detected at the center of HESS J1427−608 with a hard spectral index Γ GeV = 1.87 ± 0.17 and an integrated flux of Φ GeV = (3.06 ± 0.73) × 10 −10 photon cm −2 s −1 (Guo et al 2017). Figure 1 (left) shows the HGPS significance map with the associated X-ray and GeV sources overlaid.…”
Section: Application On Hess J1427−608 and Hess J1458−608supporting
confidence: 58%
See 2 more Smart Citations
“…No associated X-ray point source with similar column density was reported using XMM-Newton data (Fujinaga et al 2013). Above 3 GeV, a Fermi-LAT point source was detected at the center of HESS J1427−608 with a hard spectral index Γ GeV = 1.87 ± 0.17 and an integrated flux of Φ GeV = (3.06 ± 0.73) × 10 −10 photon cm −2 s −1 (Guo et al 2017). Figure 1 (left) shows the HGPS significance map with the associated X-ray and GeV sources overlaid.…”
Section: Application On Hess J1427−608 and Hess J1458−608supporting
confidence: 58%
“…Figure 2 (left) shows the corresponding spectral energy distributions (SEDs) reported in the Fermi-LAT catalogs. The spectrum of the point source detected above 3 GeV (Guo et al 2017) smoothly connects to the H.E.S.S. measurements while the 4FGL catalog reports a source with a pulsar-like spectrum represented by a logarithmic parabola.…”
Section: Multiwavelength Constraintsmentioning
confidence: 53%
See 1 more Smart Citation
“…The largest discrepancy in fit values is for the source HESS J1427-608, which had a best-fit spectral index of 2.20 in Aharonian et al (2008). Guo et al (2017) reported on a counterpart seen in Fermi-LAT data at GeV energies with a best fit including the H.E.S.S. data from Aharonian et al (2008) of E −2 over four orders of magnitude in energy with no break in the spectrum, a property unique among currently known TeV sources.…”
Section: Discussionmentioning
confidence: 97%
“…RX J1713.7-3946 (Abdo et al 2011;Yuan et al 2011;Zeng et al 2017), RX J0852-4622 (Vela Junior; Tanaka et al 2011), and RCW 86 . These SNRs are believed to be a class of sources with leptonic origin of the γ-ray emission (Yuan et al 2012;Funk 2015;Guo et al 2017).…”
Section: Discussionmentioning
confidence: 99%